Route chart : Chicago, Illinois to Gander, Newfoundland (2201) / compiled and printed by the U.S. Coast and Geodetic Survey - U.S. Coast and Geodetic Survey (U.S. Coast and Geodetic Survey (Washington), 1947)
Relief shown by gradient tints, hachures, and spot heights. Base map with aeronautical overprinting in purple. North oriented to the upper right. "Advance edition January 3, 1947." "Location of isogonic lines as of 1947 Aeronautical Information Jan. 3, 1947." "Base no. 1." "A-3217-3 (1)++." Color 1:2,000,000